Impact of the Pre-Operative Standardized Nutritional Protocol in Infants with Congenital Heart Disease (CHD) - Patrick Zacharias; Jenna Blinci; Ruthie Shenoy; Jesse Lee; Yogen Singh (Journal of Cardiovascular Development and Disease)
Neonates with congenital heart disease (CHD) are at increased risk of growth failure and necrotizing enterocolitis (NEC), making nutritional management crucial for their outcomes. This study aimed to evaluate the impact of a standardized feeding protocol on growth and NEC incidence in CHD infants. A retrospective study was conducted at a tertiary care center, including neonates diagnosed with CHDs from January 2020 to March 2023. Patients were divided into two groups: those receiving the standardized feeding protocol (protocol group, n = 12) and those who did not (non-protocol group, n = 39). Key metrics such as growth velocity at discharge, anthropometric z score changes at discharge since birth, days to full enteral feeds, NEC incidence, and length of stay were analyzed. Statistical comparisons were made using two-tailed Mann-Whitney test and chi-squared tests. The NEC incidence was 10% in the non-protocol group and 0% in the protocol group (p = 0.25), with no significant difference. All anthropometric growth markers at the time of discharge differed between the groups, with the protocol group demonstrating favorable outcomes across all measured variables; however, these differences did not reach statistical significance. The time to reach full enteral feeds was shorter (8.5 days vs. 11 days; p = 0.22), and length of stay was shorter in the protocol group (17 days vs. 23 days; p = 0.14), although neither was statistically significant. Although the protocol group showed trends towards reduced NEC and improved growth, this was not statistically significant, which could have been because of the small sample size. Our findings suggest that a standardized feeding protocol may reduce the time to full enteral feeds and hospital stay, but further large-scale studies are needed to confirm these results.